HUBUNGAN ILMU FIQIH DENGAN ILMU PENGETAHUAN LAINNYA - ., Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2021)
Fiqh is that he is not a revelati on from heaven. Fiqh is an ijti had product. The question of who defines it, for what purpose, in what social conditions is formulated, and in what geographical locus, by what apistemology, is quite influential in the process of fiqh formation. In other words, fiqh does not grow in empty space, but moves in the course of history.each fiqh considers the product always and interactio between the thinker and the sociocultural and sociopolitikal environment that surrounds it. This article was writteng using the literature reviewmethodology. Unfortunately the fiqh books that circulate widely inthe environment of muslims today can not be far from what was writt an by scientists before. Fiqh muslims today are still dominated by many medieval fiqh formulated by Middle Eastern Scientists.